FinTech Lending and Bank Credit Access for Consumers - Balyuk, Tetyana (Management Science, 2023)
Using a unique setting of an online peer-to-peer lender, I show that banks expand credit access for consumers who obtain FinTech loans. Consistent with FinTech relieving information frictions, this effect is stronger for more credit-constrained consumers. Many borrowers, especially higher-quality ones, use peer-to-peer loans to repay expensive revolving debt. Yet, debt financing and credit score changes cannot fully explain higher bank credit. The increase in bank credit access is stronger when information sets between banks and peer-to-peer lenders diverge more. These results highlight information spillovers as a novel mechanism through which FinTech lending can relieve financial constraints for consumers. This paper was accepted by Tomasz Piskorski, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2022.4319 .